1999
DOI: 10.1143/jjap.38.4608
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Research on Mercuryless Fluorescent Lamps I – Inner Electrode Operation with Pulsed Discharge –

Abstract: The characteristics of xenon-neon discharge fluorescent lamps with inner electrodes are described in this paper. All lamps were operated by pulsed discharge. When the partial pressure of neon is high, the ignition voltage and operation voltage are low because of the Penning effect. Thus, a higher mixing ratio of neon is desirable for lower ignition and operation voltages. However, the luminance of phosphor increases as the mixing ratio of xenon increases. As the pressure of xenon increases, the second peak of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Here let us discuss on the decay of phosphor afterglow. During the afterglow period, the phosphor is mainly excited by the 172 nm radiation of xenon excimers [2]. The xenon excimers are produced by the three-body collision among xenon atoms and metastable xenon, that is Xe m + 2Xe → Xe * 2 + Xe, where Xe m denotes a matastable xenon atom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here let us discuss on the decay of phosphor afterglow. During the afterglow period, the phosphor is mainly excited by the 172 nm radiation of xenon excimers [2]. The xenon excimers are produced by the three-body collision among xenon atoms and metastable xenon, that is Xe m + 2Xe → Xe * 2 + Xe, where Xe m denotes a matastable xenon atom.…”
Section: Resultsmentioning
confidence: 99%
“…However, low-pressure xenon fluorescent lamps have not yet obtained sufficient luminance. Authors have studied xenon pulsed discharge lamps and have already reported that the phosphor is mainly excited by the excimer radiation of 172 nm at the afterglow period [1,2]. In this study, the spectroscopic characteristics of radiations from xenon pulsed plasma are measured and explained by a rate equation determined experimentally as a study on a mercury-free fluorescent lamp.…”
Section: Introductionmentioning
confidence: 96%
“…Several properties of mercury are hereby utilized such as a high vapour pressure and the strong and efficient radiation in the visible and especially the ultraviolet spectral range. Recent research both in low and high pressure lamps ( [1,2,3] and [4,5]) focuses on finding efficient substitutes for mercury due to its toxicity. Molecular radiation -especially from metal halides -is under discussion to be a good alternative to mercury [6].…”
Section: Introductionmentioning
confidence: 99%
“…D UE to the potential for environmental regulations, there has recently been substantial interest in nonmercury plasma discharges for lighting applications. In the standard low-pressure fluorescent bulb, xenon [1], or pulsed xenon-neon mixtures are under investigation as replacements for Hg [2]. Such rare gas fills require new phosphors and affect the electrode behavior [2], [3].…”
mentioning
confidence: 99%
“…In the standard low-pressure fluorescent bulb, xenon [1], or pulsed xenon-neon mixtures are under investigation as replacements for Hg [2]. Such rare gas fills require new phosphors and affect the electrode behavior [2], [3]. In high-pressure discharges, metallic zinc has been studied as a mercury replacement as it is also a group IIB element in the periodic table [4].…”
mentioning
confidence: 99%